Antiviral activity of recombinant ankyrin targeted to the capsid domain of HIV-1 Gag polyprotein - Nangola S. (2014)
Background: Ankyrins are cellular mediators of a number of essential protein-protein interactions. Unlike intrabodies, ankyrins are composed of highly structured repeat modules characterized by disulfide bridge-independent folding. Artificial ankyrin molecules, designed to target viral components, might act as intracellular antiviral agents and contribute to the cellular immunity against viral pathogens such as HIV-1.Results: A phage-displayed library of artificial ankyrins was constructed, and screened on a polyprotein made of the fused matrix and capsid domains (MA-CA) of the HIV-1 Gag precursor. An ankyrin with three modules named Ank GAG1D4 (16.5 kDa) was isolated. Ank GAG1D4 and MA-CA formed a protein complex with a stoichiometry of 1:1 and a dissociation constant of K d~ 1 μM, and the Ank GAG1D4 binding site was mapped to the N-terminal domain of the CA, within residues 1-110. HIV-1 production in SupT1 cells stably expressing Ank GAG1D4 in both N-myristoylated and non-N-myristoylated versions was significantly reduced compared to control cells. Ank GAG1D4 expression also reduced the production of MLV, a phylogenetically distant retrovirus. The Ank GAG1D4-mediated antiviral effect on HIV-1 was found to occur at post-integration steps, but did not involve the Gag precursor processing or cellular trafficking. Our data suggested that the lower HIV-1 progeny yields resulted from the negative interference of Ank GAG1D4-CA with the Gag assembly and budding pathway.Conclusions: The resistance of Ank GAG1D4-expressing cells to HIV-1 suggested that the CA-targeted ankyrin Ank GAG1D4 could serve as a protein platform for the design of a novel class of intracellular inhibitors of HIV-1 assembly based on ankyrin-repeat modules. © 2012 Nangola et al; licensee BioMed Central Ltd.